Motivation and Impact of Marriage of UIN Ar-Raniry Banda Aceh Students in Hifz Ird̄i Review - Muhaiminu Laila Fitri; Zaiyad Zubaidi; Shabarullah Shabarullah; Fatima Zohra Aouati; Dalia Pervin (Yayasan Cendekia Gagayunan Indonesia, 2026)
This study aims to analyze the phenomenon of marriage among female students of UIN Ar-Raniry Banda Aceh during the study period through the perspective of hifz al-'ird in maqashid al-shariah, which is a principle that emphasizes the maintenance of honor and self-dignity. This phenomenon is interesting to study because of the increasing choice of marriage during college which gives rise to academic, social, and religious dynamics for female students. The study used a descriptive qualitative method with data collection techniques in the form of in-depth interviews with three married female students during the study period and documentation as supporting data. The data were analyzed thematically to identify the driving factors, impacts, and relevance to the concept of hifz al-'ird. The results of the study showed that the decision to marry was influenced by religious motivation, family support, mental and emotional readiness, economic considerations, and the desire to have a supportive partner in academic and household life. In terms of impact, marriage provides a positive influence in the form of moral protection, emotional support, increased responsibility, and more targeted social relations; But it also presents challenges such as the division of time between studies and household, potential academic obstacles, limited social interaction, and a decrease in focus on learning in certain situations. In the perspective of hifz al-'ird, marriage during the study period is understood as a means of maintaining honor, dignity, and personal integrity in line with the purpose of maqashid al-sharia in protecting the moral, psychological, and social aspects of individuals. The study recommends that universities provide academic support and family counseling for married female students during their studies to maintain a balance between academic responsibilities and home life.